Mechanism and Potential of Extracellular Vesicles Derived From Mesenchymal Stem Cells for the Treatment of Infectious Diseases - You, Jingyi; Fu, Zhou; Zou, Lin (Frontiers in Microbiology, 2021)
Extracellular vesicles (EVs) are nano-sized membrane vesicles secreted by cells. EVs serve as a mediator for cell-to-cell communication by regulating the exchange of genetic materials and proteins between the donor and surrounding cells. Current studies have explored the therapeutic value of mesenchymal stem cells-derived EVs (MSC-EVs) for the treatment of infectious diseases extensively. MSC-EVs can eliminate the pathogen, regulate immunity, and repair tissue injury in contagious diseases through the secretion of antimicrobial factors, inhibiting the replication of pathogens and activating the phagocytic function of macrophages. MSC-EVs can also repair tissue damage associated with the infection by upregulating the levels of anti-inflammatory factors, downregulating the pro-inflammatory factors, and participating in the regulation of cellular biological behaviors. The purpose of this mini-review is to discuss in detail the various mechanisms of MSC-EV treatment for infectious diseases including respiratory infections, sepsis, and intestinal infections, as well as challenges for implementing MSC-EVs from bench to bedside.